On necessary conditions for the weak regularity of a linear extension of a dynamical system on a torus - Grechko, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We give a necessary condition for the weak regularity of a linear extension of a dynamical system on a torus in the form of Fourier series with respect to a part of the variables.